Laboratory studies and preliminary field evaluation of vaccination trials against pasteurellosis in ducks - RAMANATHA, K R (The Indian Journal of Animal Sciences, 2013)
Formalin-inactivated, alum-adsorbed broth bacterin of Pasteurella multocida A: 1 from ducks was tested in laboratory and field trials. An indirect haemagglutination (IHA) test using glutaraldehyde-fixed sheep erythrocytes sensitized with crude capsular polysaccharide was conducted on duck sera for humoral antibody levels. The highest ranges of IHA titres of sera from once and twice vaccinated ducks were, respectively, 80-640 and 1 280-10 240 as aganist 0Â·40 from unvaccinated ducks. The IHA titres were significantly higher (P<0.001) for vaccinated over unvaccinated and twice over once vaccinated dueks and didnotdeerease significantly upto 94 day post-vaccination. Ducks vaccinated twice withstood homologous challenge with 1 740 cfu 70 days after second vaccination. Recovered ducks had IHA tubes of 10 240 to 20480 and withstood future high challenge dose of 1 07 to 10& cfu. Pasteurellosis could not be recovered from these birds. The disease in ducks was controlled by regular vaccinations and zoo-sanitary measures.